OrthoRehab: Development of a New Methodology for the Comparison Study Between Different Types of Ankle–Foot Orthoses in Foot Dysfunction - Quaresma, Cláudia; Lopes, Barbara; Jacinto, Jorge; Robalo, Tiago; Matos, Mariana; Quintão, Carla (Frontiers in Digital Health, 2021)
Foot dysfunction is one of the most likely consequences of rheumatoid arthritis and stroke. It is characterised by severe changes in the gait pattern due to a significant increase in the plantar flexion. Some of these dysfunctions can be compensated by using ankle-foot orthosis. However, the clinical decisions about which orthosis best suits the patient needs is a real problem for physicians/therapists. Purpose The main goal of this paper is to present a quantitative support tool that can assist the physicians/therapists in deciding which orthosis is most suitable for each subject. Methodology In order to achieve this goal, a platform namely OrthoRehab was developed, and it was tested in three conditions: without any orthosis and with two different dynamic ankle-foot orthoses - B and A. The data was acquired in the Gait Laboratory of Rehabilitation Medicine Center of A. using a VICON NEXUS 1.8.5® motion capture system that allows the capturing of kinematic and kinetic data. Results The results reveal that OrthoRehab is a user-friendly, easy to apply tool which analyses very relevant data for the clinical staff. Conclusion The developed decision support tool, OrthoRehab, offers a quantitative analysis and provides insight to which orthosis achieved the best performance in comparison with the patient's gait pattern with no orthosis.